Legal Protection for Healthcare Workers Against Workplace Violence in Indonesian Hospital Governance - Dame Lestaria; Ahmad Jamaludin (LifeSciFi, 2026)
Workplace violence against healthcare workers remains a persistent risk in health facilities, negatively impacting occupational safety, service quality, and institutional accountability. This research analyzes the scope of legal protection for healthcare workers in cases of violence, using one of the cases in public controversy as a contextual entry point to discuss the full spectrum of violence. The study aims to map the legal framework governing healthcare workers’ protection, examine hospitals’ responsibilities in prevention and response, and formulate feasible protection mechanisms and operational policy recommendations. Utilizing a normative-juridical approach with statutory and conceptual frameworks, the analysis indicates that Law Number 17 of 2023 concerning health explicitly recognizes healthcare workers’ rights to legal protection and occupational safety. However, significant implementation gaps persist at the institutional level, including weak reporting channels, inconsistent standard operating procedures, and insufficient anti-retaliation safeguards. The study concludes that effective protection requires translating statutory rights into robust operational hospital governance through zero-tolerance policies, integrated incident reporting and investigation systems, and comprehensive recovery support for victims.